1995
DOI: 10.1136/bjo.79.7.664
|View full text |Cite
|
Sign up to set email alerts
|

Sleeves for fixation of Silastic nasolacrimal tubes.

Abstract: Aims-To describe a method of securi indwelling O'Donohughe's lacrimal tul in dacryocystorhinostomy using two 3 mm Watski sleeves Methods-The operative technique us to secure the sleeves into position on 1 lacrimal tubes is described. Forty sev procedures with a follow up ranging fr( 3 to 30 months (mean 10 months) E reviewed. Results-The tubes and sleeves were M tolerated. Upward prolapse of the tul occurred only once and the tubes wt easily repositioned in this case. Conclusion-Securing lacrimal tul with Wats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Reported rates of stent prolapse range from 10% to 17%. 2 Rates of stent extrusion at the authors' institution are consistent with those reported in the literature. Silicone stent prolapse often requires repositioning or premature removal.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Reported rates of stent prolapse range from 10% to 17%. 2 Rates of stent extrusion at the authors' institution are consistent with those reported in the literature. Silicone stent prolapse often requires repositioning or premature removal.…”
supporting
confidence: 88%
“…1 A number of techniques have been described to minimize premature stent prolapse, principally the use of anchoring sutures or a foreign body as a stopper. 2,3,5,11 The Bartley technique of intubating the internal ostium and nasolacrimal duct provides 2 outflow pathways, prevents internal ostium closure, and reduces the risk of stent extrusion. However, the outer diameter of the silicone stent determines the eventual luminal diameter of the nasolacrimal duct and internal ostium.…”
Section: Discussionmentioning
confidence: 99%
“…Various sets and methods have been described for lacrimal intubation (9-11). The O'Donough intubation set in Europe, (12,13) and Quickert (9) or Crawford (11) sets in the United States are the most commonly preferred. In these sets, silicone tubes are attached to metal probes ranging in length from 45 mm to 177 mm.…”
Section: Discussionmentioning
confidence: 99%
“…With the widespread use of intubation in routine DCR, many problems have been reported in the literature with stents including granuloma formation, nasal irritation, punctal cheese-wiring, nasal bleeding, chronic infections, corneal erosions and displacement (7)(8)(9)(10). Stent prolapse is an important complication with a reported incidence of up to 17% (10).…”
Section: Introductionmentioning
confidence: 99%
“…Stent prolapse is an important complication with a reported incidence of up to 17% (10). This problem of stent displacement is more likely to be prevalent among the pediatric population due to rubbing of the eyes or pulling it out from the medial canthal end.…”
Section: Introductionmentioning
confidence: 99%